Patterns of nurse–physician communication and agreement on the plan of care. Issue 3 (29th April 2010) - O'Leary, K J; Thompson, J A; Landler, M P; Kulkarni, N; Haviley, C; Hahn, K; Jeon, J; Wayne, D B; Baker, D W; Williams, M V
Abstract : Background: Interdisciplinary communication is critically important to provide safe and effective care, yet it has been inadequately studied for hospitalised medical patients. Our objective was to characterise nurse–physician communication and their agreement on patients' plan of care. Methods: During a one-month period, randomly selected hospitalised patients, their nurses and their physicians were interviewed. Nurses and physicians were asked to identify one another, whether communication had occurred, and about six aspects of the plan of care. Two internists rated nurse–physician agreement on aspects of the plan of care as none, partial or complete agreement. Measures included the percentage of nurses and physicians able to identify one another and reporting communication and the percentage of nurse–physician pairs in agreement on aspects of the plan of care. Results: 310 (91%) and 301 (88%) of 342 eligible nurses and physicians completed interviews. Nurses correctly identified patients' physicians 71% of the time and reported communicating with them 50% of the time. Physicians correctly identified the patients' nurses 36% of the time and reported communicating with them 62% of the time. Physicians and nurses showed no agreement on aspects of the plan of care ranging from 11% for planned procedures to 42% for medication changes. Conclusions: Nurses and physicians did not reliably communicate with one another and were often not in agreement on the plan of care for hospitalised medical patients.